Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
[tex]4 {a}^{3} - a {}^{2} = 2 {a }^{2} \\ a {}^{2} (4a - 1) = 2 \times {a}^{2} \\ 4a - 1 = 2 \\ 4a = 2 + 1 \\ 4a = 3 \\ a = \frac{3}{4} [/tex]
Answer:
the three solutions are 0, 0 and 3/4.
Step-by-step explanation:
Solve 4a^3-a^2=2a^2.
Rewrite this so that all terms are on the left with the exception of 0 on the right: 4a^3 - a^2 - 2a^2 = 0
Combining like terms, we get
4a^3 - 3a^2 = 0
Recognize that these two terms have the common factor a^2. Thus, this 4a^3-a^2=2a^2 becomes (a^2)(4a - 3) = 0, and so the three solutions are 0, 0 and 3/4.
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.